Changes in blood lactate concentration during active recovery at sub-lactate threshold, lactate threshold, and supra-lactate threshold exercise intensities. - Weihrer, Sylvia J. (University of Ottawa (Canada), 1991)
The purpose of this investigation was to identify the intensity of recovery exercise, relevant to endurance event performance, that would result in the most rapid times for half decrease in blood lactate concentration, following 2 minutes of cycling at maximal rates. Three recovery exercise intensities were investigated: (a) 7% of the maximal rate of oxygen consumption (VO$\sb2$) (LT $-$7%), (b) lactate threshold VO$\sb2$ ( LT), and (c) 7% of VO$\sb2$max above lactate threshold VO$\sb2$ (LT +7%). Seven well-trained male cyclists (mean VO$\sb2$max 4.6 $\pm$ 0.49 L $\times$ min$\sp{-1}$ participated as subjects in the investigation. Each subject completed seven separate cycling tests: (a) one combined lactate threshold-VO$\sb2$max test, (b) three constant work rate tests, and (c) three tests of recovery following supra-lactate threshold exercise (surge-recovery tests). The absolute values of blood lactate concentration were significantly different across the three recovery intensities (p .01). At the end of the 20 minute recovery period the mean blood lactate concentrations were 1.57, 2.49, and 4.17 mmol $\times$ L$\sp{-1}$ for the LT $-$7%, LT%, and LT +7% recovery intensities, respectively. Times for half decrease in blood lactate concentration were calculated. There were no significant differences in these half decrease times between the three recovery intensities (p .01). (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.